Evaluation of thermal performance in Pulsating Heat Pipe cooling system - Guragain, Kushal; Badu, Prakash; Bastakoti, Durga; Chhetri, Sunita; Baral, Kapil; Bhattarai, Rajesh (Journal of Innovations in Engineering Education, 2023)
The effectiveness of the pulsating heat pipe’s is one of many concerning factor in accessing thermal performance is contingent on various physical parameters, namely diameter, length, numbers of turn, heat inputs, and fill ratios of the heat pipe. Both experimental and numerical modeling approaches were employed to investigate a single-loop heat pipe, aiming to determine the thermal resistance at fill ratios of 40%, 50%, and 60% for water. This investigation was conducted under conditions of fluctuating temperature inputs, specifically at 378K, 383K, 388K, and 393K. The experiment was conducted for a copper pipe of inner diameter 4.0625mm and, at the evaporator heat input was supplied 45W. It was found experimentally that the thermal resistance was lowest for the case of 60% FR at 393K (i.e., 0.762K/W) after all the systems were stable but initially at the startup phase thermal resistance was lowest for the case of 50% at 393K (i.e., 1.279K/W). The analysis through numerical simulation included the examination of the temperature variation between the evaporator (T e ) and condenser (T c ), thermal resistance (R th ), the pulsating nature of the heat pipe, phase change of the working fluid, and fluid flow behavior. The thermal resistance obtained through numerical modeling is found to be lowest for a 50% FR at 393K (i.e., 1.032K/W) which resembles the initial startup phase. To confirm the occurrence of a two-phase phenomenon inside the PHP, the volume fraction of water in evaporator region was obtained from simulation results and was plotted against the time step. Observation of the oscillating motion in the PHP was conducted through a numerical model and affirmed by the upward movement of the vapor bubble toward the condenser, as well as the velocity vector contour at a specific cross-section of the pipe. The fluctuation in temperature observed in both the evaporator and condenser provides evidence that the liquid and vapor slugs oscillate along the pipe, facilitating the transport of heat from evaporator section to condenser. This experiment suggests that the best case within the tested working condition is for a 60% FR at 393K.